Necessity of anti-circumvention rules in Korean antidumping procedures - Baik, Seung-Gwon (KDI School, 1998)
This dissertation presents some of the practical problems experienced in the procedures of the antidumping duties, and continues with suggestions for the necessity of introducing anti -circumvention rules in Korean antidumping procedures. Dumping is the sale of a product for export at a pnce less than its normal value. Despite the pursuit of the free trade principle, GATT Article VI allows WTO Members to take discriminatory and remedial measures against the unfair trade practices of trade partners. One of the remedial measures is an antidumping duty. However, exporters are attempting to circumvent the antidumping duty orders. One of the key goals of the U.S. and the EU in negotiating new provisions in the GATT Antidumping Code was to adopt a specific provision permitting WTO Members to address the circumvention of antidumping duty orders. At the end of the day, however, a consensus simply could not be reached on the issue. Rather, the most that the U.S. and EU could get was statement in the Ministerial Declaration issued at Marrakesh. And pursuant to the Ministerial Decision, the Informal Group on Anti-Circumvention was established by the Committee on Antidumping Practices. Now the Informal Group is trying to seek uniform rules on anti-circumvention. After the WTO entered into force m j anuary 1995, Korea has no longer victimized by antidumping actions. Indeed, many Korean comparues are now being injured by dumped exports from China, Southeast Asian countries and Japan. In 1997, Korea was also party to an antidumping case that was related with anti- circumvention, namely, a case involving "non- refillable disposable pocket lighters" from China. And despite the absence of multilateral rules, a number of countries have adopted anti-circumvention provisions unilaterally. Thus, this paper s uggests that Korea needs to adopt anti - circumvention rules to effectively enforce the antidumping duties that it imposes
Thesis(Master)--KDI School:Master of International Economic Policy,1998